Free‐riding in multi‐party alliances: The role of perceived alliance effectiveness and peers' collaboration in a research consortium - Fonti, Fabio; Maoret, Massimo; Whitbred, Robert (Strategic Management Journal, 2017)
Research summary : Multi‐party alliances rely on partners' willingness to commit and pool their efforts in joint endeavors. However, partners face the dilemma of how much to commit to the alliance. We shed light on this issue by analyzing the relationship between partners' free‐riding—defined as their effort‐withholding—and their perceptions of alliance effectiveness and peers' collaboration. Specifically, we posit a U‐shaped relationship between partners' subjective evaluations of alliance effectiveness and their free‐riding. We also hypothesize a negative relation between partners' perceptions of the collaboration of peer organizations and their free‐riding. Results from a mixed‐method study—combining regression analysis of primary data on a major inter‐organizational research consortium and evidence from two experimental designs—support our hypotheses, bearing implications for the multi‐party alliances literature . Managerial summary : Free‐riding is a major concern in multi‐party alliances such as large research consortia, since the performance of these governance forms hinges on the joint contribution of multiple partners that often operate according to different logics (e.g., universities, firms, and government agencies). We show that, in such alliances, partners' perceptions have relevant implications for their willingness to contribute to the consortium's shared goals. Specifically, we find that partners free‐ride more—that is, contribute less—when they perceive the effectiveness of the overall alliance to be either very low or very high. Partners also gauge their commitment to the alliance on the perception of the effort of their peers—that is, other organizations similar to them. These findings provide managers of multi‐party alliances with additional levers to motivate partners to contribute fairly to such joint endeavor . Copyright © 2015 John Wiley & Sons, Ltd.